Simultaneous Improvements of Gain and Linearity in Dispersion-Tolerant Phase-Modulated Analog Photonic Link - Zhipeng Xie; Song Yu; Shanyong Cai; Wanyi Gu (IEEE Photonics Journal, 2017)
A high-gain, dispersion-tolerant, and linear phase-modulated analog photonic link is proposed and demonstrated based on full spectrum optical sideband processing (FSOSP). In the proposed link, upper sidebands and lower sidebands are transmitted separately in different optical paths. By suppressing the optical carrier, this link can be linearized. Moreover, it can be dispersion-tolerant due to single-sideband modulation, and it can be high-gain due to reflected spectrum reuse and power enhancement of upper and lower optical sidebands as the suppression power of optical carrier is compensated. Additionally, gain and spurious-free dynamic range are experimentally improved by 15.52 and 25.06 dB, respectively, in the proposed dispersion-tolerant link, as compared to that in a conventional phase-modulated link without FSOSP.